Analisis Naratif Lirik Lagu Tak Selalu Memiliki dalam Studi Persepsi Penonton Fim Ipar adalah Maut - Melani Ningsih; Leili Kurnia Gustini (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the narrative meaning of the lyrics in the song Tak Selalu Memiliki from the perspective of viewers of the film Ipar adalah Maut. Utilizing a qualitative approach with a phenomenological method, the research explores the lived experiences of five informants who have watched the film & listened to the featured song. Data were collected through in-depth interviews & analyzed using thematic techniques to uncover emotional connections & constructed meanings in the viewers’ minds. The findings reveal that the lyrics of Tak Selalu Memiliki contain narratives of loss, sacrifice, & helplessness, which strengthen the moral message of the film Ipar adalah Maut. The song is perceived as an emotional representation that deepens the audience’s understanding of the characters’ inner conflicts. This study concludes that music can serve as a reflective medium that enriches the interpretation of a film’s narrative.